2018
DOI: 10.1002/uog.18836
|View full text |Cite
|
Sign up to set email alerts
|

Sonographers' self‐reported visualization of normal postmenopausal ovaries on transvaginal ultrasound is not reliable: results of expert review of archived images from UKCTOCS

Abstract: ObjectiveIn the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS), self‐reported visualization rate (VR) of the ovaries by the sonographer on annual transvaginal sonographic (TVS) examinations was a key quality control (QC) metric. The objective of this study was to assess self‐reported VR using expert review of a random sample of archived images of TVS examinations from UKCTOCS, and then to develop software for measuring VR automatically.MethodsA single expert reviewed images archived from 1000 TVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…We have previously reported on the Quality Control (QC) of UKCTOCS TVS scanning with similar exam selection criteria (ovaries were seen and normal) 7 . A single expert reviewed 1000 randomly chosen TVS examinations which had been performed by 96 sonographers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on the Quality Control (QC) of UKCTOCS TVS scanning with similar exam selection criteria (ovaries were seen and normal) 7 . A single expert reviewed 1000 randomly chosen TVS examinations which had been performed by 96 sonographers.…”
Section: Discussionmentioning
confidence: 99%
“…A metric commonly used in the quality control (QC) of TVS is self-reported visualisation rate (VR), defined as the number of examinations in which the ovaries were visualized as a proportion of all examinations performed by the sonographer 7 . In 2008, UKCTOCS implemented an accreditation programme which included the monitoring of individual sonographer VR over a 3 month period 8 .…”
Section: Introductionmentioning
confidence: 99%
“…While well-trained imagers can obtain concordant results, 78 re-review of 1,000 archived cases with apparently normal morphology from the early years of the UKCTOCS indicated unsatisfactory visualization of the ovaries and tubes in 50% of cases. 79 Imaging of the fallopian tubes, the site of origin of at least one third of high grade serous ovarian cancers, can be particularly difficult in the absence of conditions that cause thickening of the tube or accumulation of intra-luminal fluid. Even in the most expert centers, fallopian tubes could not be visualized in 23% of 549 healthy women.…”
Section: Screening Symptomatic Womenmentioning
confidence: 99%
“…Studies have shown that multidrug resistance-associated protein 1 (MRP1), glutathione S-transferase π (GST-π), and glycogen synthase kinase-3β (GSK3β) may be associated with chemotherapy resistance and prognosis of ovarian cancer (68). As a transmembrane protein-encoding gene, MRP1 is able to cause drug resistance mainly by reducing the intracellular concentration of drugs (9).…”
Section: Introductionmentioning
confidence: 99%